Determinants of Foreign Direct Investment in the Malaysian Manufacturing Sector - Yusop, Zulkarnain; Abdul Ghaffar, Roslan (Universiti Putra Malaysia Press, 1994)
Foreign direct investment (FDI) has played a significant role in the development of the Malaysian manufacturing sector. Unfortunately, the pattern of FDI is unevenly concentrated in a few industries such as electrical and textile which involve less skilled labour, less intensive technology and are highly dependent on imported inputs. This has led to the problems associated with a narrow manufacturing base, vulnerability to external fluctuations as well as low value added. It is therefore necessary to promote a broader manufacturing base and to further encourage FDl in resource-based industries. This study attempts to look at several quantitative factors that influence FDI in the Malaysian manufacturing sector. The results of the study indicate that a nation's economic health, currency stability, access to local financing, availability of adequate human and physical infrastructures as well as investment incentives are among the important factors influencing FDI in the manufacturing sector of Malaysia